2012
DOI: 10.1016/j.intermet.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the LPSO phase of the 14H-type in the Mg–Al–Gd alloy system

Abstract: The crystal structure of a long-period stacking-ordered (LPSO) phase of the 14H type formed in a Mg-Al-Gd alloy as a local small part in the intergrowth structure together with that of the 18R type (the majority) has been investigated by scanning transmission and transmission electron microscopy. The LPSO phase of the 14H type in the Mg-Al-Gd system is found to form by stacking structural blocks, each of which consists of seven close-packed atomic planes. In each of structural blocks, a long-range ordering occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Various types of the LPSO phases expressed as 10H, 14H, 18R and 24R-types, which are formed by stacking structural blocks composed of five, six, seven and eight close packed atomic layers, respectively, have been reported in various Mg-Zn-RE systems [8][9][10][11][12][13][14][15][16]. The crystal structures of the Mg-TM-RE LPSO phases have been generally characterized by the periodic stacking faults associated with the enrichment of TM and RE atoms in two consecutive atomic layers [9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of the LPSO phases expressed as 10H, 14H, 18R and 24R-types, which are formed by stacking structural blocks composed of five, six, seven and eight close packed atomic layers, respectively, have been reported in various Mg-Zn-RE systems [8][9][10][11][12][13][14][15][16]. The crystal structures of the Mg-TM-RE LPSO phases have been generally characterized by the periodic stacking faults associated with the enrichment of TM and RE atoms in two consecutive atomic layers [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of the Mg-TM-RE LPSO phases have been generally characterized by the periodic stacking faults associated with the enrichment of TM and RE atoms in two consecutive atomic layers [9,12]. It should be noted that the Ramdell's notations used to describe the LPSO structures are assigned under an assumption that all close-packed atomic layers are identical, which are in fact not adequate in a strict crystallographic sense because of the RE and TM enrichment in some of the close-packed atomic layers [9,[12][13][14][15][16][17][18]. However, the above mentioned Ramsdell notations have been utilized because no atomic ordering in any closepacked atomic layers was considered to exist originally.…”
Section: Introductionmentioning
confidence: 99%
“…The cluster formations are observed in the more stable LPSO structure, for instance, in the MgAl Gd system. 13) In the MgZnY system, such a clear cluster formation has not been observed as it is under discussion.…”
Section: Interaction Energy Between Two Pairs Of Znymentioning
confidence: 92%
“…For an 18R-LPSO phase, it was suggested that the clusters formed partially ordered domain structures [23][24][25] even though they did not exhibit long-range ordering in directions parallel and perpendicular to the stacking direction [23,26]. In contrast, in a 10H-LPSO phase of Mg-Zn-Y alloys, the clusters show long-range ordering in the direction perpendicular to the stacking direction, i.e., inside the ABCA-type stacking layers [19]; the ordered arrangement of clusters is similar to the order-disorder (OD) structure formed in Mg-Al-Gd alloys [26,27].…”
Section: Introductionmentioning
confidence: 88%